Preparation method of high-compactness and high-stability conductive polymer film based on electrochemical polymerization

The chemical foil is pretreated and electrochemically polymerized by electrochemical polymerization, which solves the problem of inter-chain gaps caused by irregular arrangement of rigid chains during the film formation process of PBFDO film, improves the density and stability of the film, reduces the leakage current and equivalent series resistance of the aluminum electrolytic capacitor, and enhances the high temperature and high humidity stability of the device.

CN119800385AActive Publication Date: 2025-04-11JURONG OPTOELECTRONICS (GUANGZHOU) NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411991980.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the film formation process, existing PBFDO films have problems with inter-chain gaps due to irregular arrangement of rigid chains, and film quality and stability are especially prone to fall off in humid environments, resulting in an increase in leakage current of aluminum electrolytic capacitors and an increase in equivalent series resistance.

Method used

The chemical foil is pretreated by the treatment liquid by the treatment liquid, including repeated impregnation and drying in the oxidant solution and the BFDO monomer solution to form a pretreatment and melting foil containing the N-type conductive polymer PBFDO, and then electrochemically polymerized in the three-electrode system to prepare a conductive polymer film with high density and high stability.

Benefits of technology

It improves the density and stability of the conductive polymer film, reduces the leakage current and equivalent series resistance of the aluminum electrolytic capacitor, enhances the high temperature and high humidity stability of the device, and meets the application needs of high reliability and high performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800385A_ABST
    Figure CN119800385A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-compactness and high-stability conductive polymer film based on electrochemical polymerization, which comprises the following steps: pretreating a formed foil by using an oxidant solution and a BFDO monomer solution to obtain a working electrode, then immersing the working electrode and a reference electrode into an electrolyte, and carrying out electrochemical oxidation polymerization to obtain the conductive polymer film with high compactness and high stability. The high-compactness and high-stability conductive polymer film based on electrochemical polymerization is obtained. The pretreated formed foil containing the N-type conductive polymer PBFDO is prepared on the formed foil by using a chemical in-situ polymerization method, and when the pretreated formed foil is applied to the field of capacitors, the electric conductivity and the electron transmission capacity of the capacitors can be improved, and the stability problem caused by positive and negative charge coupling in a traditional capacitor is greatly solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of conductive polymers, and in particular to a method for preparing a conductive polymer film with high compactness and high stability based on electrochemical polymerization. Background Art

[0002] At present, conductive polymers have a wide range of applications in the field of organic electronics. Since the ultra-high conductivity and high stability N-type conductive polymer PBFDO (polybenzo[1,2-B:4,5-B']difuran-2,6(3H,7H)-dione) was reported (Nature 2022,611,271-277), the preparation of high-density thin films of PBFDO and its applications have received increasing attention. Taking chip-type laminated aluminum electrolytic capacitors as an example, aluminum electrolytic capacitors based on PBFDO have great application potential in consumer electronics, computers, information communications and automotive electronics. However, PBFDO is a rigid linear polymer molecule. During the film formation process of PBFDO prepared by chemical oxidative polymerization, the irregular arrangement of its rigid chains will lead to large gaps between molecular chains, and there are certain problems with the quality and stability of the film. In addition, the PBFDO film prepared by the chemical in-situ polymerization method has certain problems with the density and stability of the film due to the non-uniformity in the reaction process and the rigid structure of the material. It is easy to fall off when exposed to a humid environment and solvent atmosphere such as DMSO for a long time. In the preparation and actual application of aluminum electrolytic capacitors, the above situation will lead to an increase in the leakage current (LC) and equivalent series resistance (ESR) of the aluminum electrolytic capacitor, and this change is irreversible. Therefore, improving the quality and stability of PBFDO films is of great significance for the practical application of PBFDO, especially the widespread application of high-reliability and high-performance chip-type laminated aluminum electrolytic capacitors. Summary of the invention

[0003] Based on this, it is necessary to provide a method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization, and the prepared film has a more dense and smooth surface morphology. The aluminum electrolytic capacitor prepared by this method has the advantages of low leakage current (LC), small equivalent series resistance (ESR), stable capacitance, etc., and has significant economic value and social benefits.

[0004] An object of the present invention is to provide a method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization, comprising the following steps:

[0005] The forming foil is pretreated with a treatment solution to obtain a working electrode, and then the working electrode, the reference electrode and the counter electrode are immersed in an electrolyte, and electrochemical polymerization is performed through a three-electrode system to obtain a high-density and high-stability conductive polymer film based on electrochemical polymerization;

[0006] Wherein, the treatment liquid is selected from an oxidant solution and a BFDO monomer (benzo[1,2-B:4,5-B']difuran-2,6(3H,7H)-dione, CAS: 30272-74-3) solution;

[0007] or

[0008] The treatment liquid is selected from PBFDO (polybenzo[1,2-B:4,5-B']difuran-2,6(3H,7H)-dione) solution.

[0009] In one embodiment of the present invention, the pretreatment comprises the following steps:

[0010] The chemical foil is immersed in the PBFDO solution and dried. After repeating this process several times, a pretreated chemical foil is obtained.

[0011] In another embodiment of the present invention, the pretreatment comprises the following steps:

[0012] The chemical foil is immersed in an oxidant solution, dried, and then immersed in a BFDO monomer solution, dried. After repeating this process several times, a pretreated chemical foil is obtained.

[0013] In another embodiment of the present invention, the pretreatment comprises the following steps:

[0014] The chemical foil is immersed in a BFDO monomer solution, dried, and then immersed in an oxidant solution, dried. After repeating this process several times, a pretreated chemical foil is obtained.

[0015] Specifically, by directly immersing the chemical foil in a PBFDO solution, a pretreated chemical foil containing an N-type conductive polymer PBFDO can be obtained in one step; by immersing the chemical foil in an oxidant solution and a BFDO monomer solution respectively, a pretreated chemical foil containing an N-type conductive polymer PBFDO can be prepared by a chemical in-situ polymerization method.

[0016] Specifically, the time for immersing the formed foil in the PBFDO solution is 4-20 seconds;

[0017] Specifically, the time for immersing the formed foil in the oxidant solution is 4-20 seconds;

[0018] Specifically, the time for immersing the formation foil in the BFDO monomer solution is 4-20 seconds.

[0019] Furthermore, the oxidant is selected from one or more of metal salt oxidants, oxides, peroxides, quinone compounds, and acid anhydride compounds.

[0020] Wherein, the metal salt oxidant includes but is not limited to ferric chloride and cupric acetate.

[0021] The oxides include but are not limited to selenium dioxide, copper oxide, and cuprous oxide.

[0022] The peroxide includes but is not limited to hydrogen peroxide and tert-butyl hydroperoxide.

[0023] The quinone compounds include, but are not limited to, 2,3,5,6-tetramethyl-1,4-benzoquinone, 1,4-benzoquinone, and 2-(10-hydroxydecyl)-5,6-dimethoxy-3-methyl-1,4-benzoquinone.

[0024] The acid anhydride compound includes but is not limited to acetic anhydride, maleic anhydride, and benzoic anhydride.

[0025] Furthermore, the concentration of the PBFDO solution is 3-20 mg / mL.

[0026] Furthermore, the concentration of the BFDO monomer solution is 5-15 mg / mL.

[0027] Furthermore, the number of repetitions is 1-30 times.

[0028] Specifically, the pretreated chemical foil containing the N-type conductive polymer PBFDO prepared by the above process is used as a working electrode for electrochemical polymerization to further obtain a conductive polymer film with high density and high stability.

[0029] Furthermore, a three-electrode system is used in the electrochemical oxidative polymerization. The three-electrode system includes a working electrode, a counter electrode and a reference electrode. The working electrode is a pre-treated chemical foil, the counter electrode is selected from one or more of platinum and graphite electrodes, and the reference electrode is selected from one or more of saturated calomel electrode, silver chloride electrode, and mercury / mercurous sulfate electrode.

[0030] Furthermore, the electrochemical oxidative polymerization method adopts one of a constant voltage method, a constant current method, and a cyclic voltammetry method.

[0031] Specifically, in the constant voltage method, the oxidation potential is 0.3-3.0 V, and the oxidation polymerization time is 5-200 min.

[0032] Specifically, in the constant current method, the oxidation current is 0.1 μA-10 mA, and the oxidation polymerization time is 5-200 min.

[0033] Specifically, in the cyclic voltammetry, the voltage scanning range is -1.0 to 3.0 V, the scanning rate is 20-100 mV / s, and the number of cycles is 10-5000.

[0034] Further, the electrolyte is selected from a solution containing EDOT monomer (3,4-ethylenedioxythiophene) and its derivatives;

[0035] Wherein, the concentration of the solution is 5-300 mg / mL.

[0036] Specifically, the EDOT-containing monomers and their derivatives include but are not limited to 3,4-ethylenedioxythiophene (CAS: 126213-50-1), 2-methyl-2,3-dihydro-thieno[3,4-B]-1,4-dioxin (CAS: 126235-11-8), and 2-ethyl-2,3-dihydro-thieno[3,4-B]-1,4-dioxin (CAS: 1226799-20-7).

[0037] Specifically, the present invention uses an independently designed and prepared electrolyte for electrochemical polymerization, and can customize different electrolyte systems according to different application scenarios to prepare capacitor products that meet different parameters and requirements, which has wide practicality.

[0038] The present invention also provides the application of the high-density and high-stability conductive polymer film based on electrochemical polymerization prepared by the preparation method in the fields of flexible electrodes, supercapacitors, and aluminum electrolytic capacitors.

[0039] Specifically, the high-density and high-stability conductive polymer film based on electrochemical polymerization of the present invention has broad application prospects in many fields such as supercapacitors and electrolytic capacitors. Taking aluminum electrolytic capacitors as an example, the processed formed foil is subjected to the steps of carbon slurry coating, silver slurry coating, lamination bonding, epoxy resin encapsulation and aging to obtain a chip-type laminated aluminum electrolytic capacitor with low leakage current (LC), low equivalent series resistance (ESR) and high stability.

[0040] The present invention has the following beneficial effects:

[0041] 1. The present invention uses a chemical in-situ polymerization method on the chemical foil to prepare a pretreated chemical foil containing an N-type conductive polymer PBFDO. Compared with directly blending the monomer, oxidant, and solvent and then performing chemical in-situ polymerization, the present invention can meet the requirement of directly generating a conductive polymer film in-situ inside the pore, with higher surface coverage and strong substrate adhesion, and can effectively avoid the problem that the conductive polymer cannot efficiently enter the pore due to the large particle size. At the same time, it has the advantages of saving raw materials and avoiding the inability to reuse the monomer and oxidant after blending, which meets the requirements of large-scale assembly line preparation and practical application; in addition, due to the extremely poor solubility of BFDO monomer in the oxidant solution, the method of the present invention can avoid the introduction of impurities between the BFDO monomer solution and the oxidant solution during the in-situ polymerization process. When it is used in the field of aluminum electrolytic capacitors, it can improve the conductivity and electron transmission capacity of the capacitor, and greatly improve the stability problem caused by the coupling of positive and negative charges. In addition, since the N-type conductive polymer PBFDO has excellent moisture resistance, the high temperature and high humidity stability of the prepared aluminum electrolytic capacitor is also greatly improved, achieving the successful preparation of high-capacity, high-stability, and low-ESR aluminum electrolytic capacitors.

[0042] 2. By electrochemically polymerizing EDOT on a pretreated chemical foil containing an N-type conductive polymer PBFDO, the pretreated chemical foil containing an N-type conductive polymer PBFDO is modified in a low-cost, non-toxic, and low-pollution manner without introducing other impurities, thereby preparing a conductive polymer film with high density, high stability, and high conductivity. Compared with the prior art, this method can effectively avoid the performance problems caused by the application of P-type conductive polymers to the negative electrode of the capacitor, while giving full play to its advantages, electrochemically modifying the conductive polymer PBFDO layer, and making the best use of its strengths and avoiding its weaknesses; in addition, when the conductive polymer film obtained by the method provided by the present invention is applied to the field of aluminum electrolytic capacitors, it can effectively reduce the LC and ESR of aluminum electrolytic capacitors, greatly improve the device performance and stability, and has significant economic value and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The SEM test images of the formed foils D1-D6 are shown;

[0044] Figure 2 SEM test images of conductive polymer films M1-M7 are shown. DETAILED DESCRIPTION

[0045] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0046] BFDO monomer: purchased from Henan Alpha Chemical Co., Ltd., CAS: 30272-74-3.

[0047] Chemical foil: purchased from Huafeng Electronic Aluminum Foil Co., Ltd., low-voltage positive foil.

[0048] Selenium dioxide: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS: 7446-08-4.

[0049] PBFDO solution: prepared according to the literature “Tang Haoran, et al., A solution-processed n-type conducting polymer with ultrahigh conductivity. Nature, 2022, 611, 271-277.”

[0050] Preparation Example 1

[0051] The method for preparing the pretreated chemical foil comprises the following steps:

[0052] Dissolving BFDO monomer in DMSO solution to obtain a BFDO monomer solution with a concentration of 10 mg / mL;

[0053] Dissolve selenium dioxide in water to obtain an oxidant solution with a concentration of 10 mg / mL;

[0054] The formed foil was immersed in the oxidant solution for 20 seconds, taken out and dried at 40°C for 15 minutes, immersed in the BFDO monomer solution for 10 seconds, taken out and vacuum dried at 80°C for 15 minutes, and the above steps were repeated for 10 cycles to obtain the 10-times pretreated formed foil D1.

[0055] Preparation Example 2

[0056] The method for preparing the pretreated chemical foil comprises the following steps:

[0057] Dissolving BFDO monomer in DMSO solution to obtain a BFDO monomer solution with a concentration of 12 mg / mL;

[0058] Dissolve copper acetate in ethanol to obtain an oxidant solution with a concentration of 6 mg / mL;

[0059] The formed foil was immersed in the oxidant solution for 5 seconds, taken out and vacuum dried at 80°C for 15 minutes, then immersed in the BFDO monomer solution for 5 seconds, taken out and allowed to stand at room temperature for 15 minutes to dry, and the above steps were repeated for 10 cycles to obtain the 10-times pretreated formed foil D2.

[0060] Preparation Example 3

[0061] The method for preparing the pretreated chemical foil comprises the following steps:

[0062] Dissolving BFDO monomer in DMSO solution to obtain a BFDO monomer solution with a concentration of 10 mg / mL;

[0063] Dissolve selenium dioxide in isopropanol to obtain an oxidant solution with a concentration of 10 mg / mL;

[0064] The formed foil was immersed in the oxidant solution for 5 seconds, taken out and vacuum dried at 80°C for 15 minutes, then immersed in the BFDO monomer solution for 5 seconds, taken out and allowed to stand at room temperature for 15 minutes to dry, and the above steps were repeated 10 times. Then, the formed foil was immersed in the finished PEDOT:PSS solution (commonly available commercially, 1.5wt% pure aqueous solution) for 5 seconds. After being immersed in deionized water for 5 seconds and vacuum dried at 80°C, the 10-times pretreated formed foil D3 was obtained.

[0065] Preparation Example 4

[0066] The method for preparing the pretreated chemical foil comprises the following steps:

[0067] Dissolving BFDO monomer in DMSO solution to obtain a BFDO monomer solution with a concentration of 10 mg / mL;

[0068] Dissolve selenium dioxide in ethanol to obtain an oxidant solution with a concentration of 10 mg / mL;

[0069] The formed foil was immersed in the BFDO monomer solution for 5 seconds, taken out and vacuum dried at 80°C for 15 minutes, then immersed in the oxidant solution for 5 seconds, taken out and allowed to stand at room temperature for 15 minutes to dry, and the above steps were repeated 25 times. Then, the formed foil was immersed in the finished PEDOT:PSS solution (commonly available, 1.5wt% aqueous solution) for 10 seconds, and after being immersed in deionized water for 5 seconds and vacuum dried at 80°C, a 10-times pretreated formed foil D4 was obtained.

[0070] Preparation Example 5

[0071] The method for preparing the pretreated chemical foil comprises the following steps:

[0072] The chemical foil was immersed in a PBFDO solution (10 mg / mL) for 3 min at room temperature and normal pressure, taken out, washed with deionized water, and vacuum dried at 80° C. to obtain a pretreated chemical foil D5.

[0073] Comparative Preparation Example 1

[0074] The method for preparing the pretreated chemical foil comprises the following steps:

[0075] BFDO monomer (150 mg) and selenium dioxide (9 mg) were dissolved in 10 mL DMSO solution, and the chemical foil was immersed in the above solution at room temperature and normal pressure for 3 minutes. After being taken out, it was washed with deionized water and vacuum dried at 80° C. to obtain the pretreated chemical foil D6.

[0076] Among them, the above mixed solution gradually gels within 10 minutes at room temperature and cannot be reused, resulting in loss of raw materials. Therefore, it does not meet the requirements of continuous and large-scale production in actual application processes, so subsequent electrochemical polymerization is not carried out.

[0077] Preparation Example 1

[0078] 5 g of EDOT monomer was added to 100 mL of ethanol solution, magnetically stirred at room temperature for 30 min, and 1 g of p-toluenesulfonic acid was added to prepare an electrolyte;

[0079] A three-electrode system was adopted, with the pretreated chemical foil D1 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode and the reference electrode were immersed in the electrolyte and subjected to an electrochemical polymerization reaction for 40 minutes at an oxidation potential of 1.6 V by the constant voltage method. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C in vacuum for 20 minutes to obtain a highly dense and highly stable conductive polymer film M1 based on electrochemical polymerization.

[0080] Preparation Example 2

[0081] A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization comprises the following steps:

[0082] 10 g of EDOT monomer was added to 100 mL of 50 wt% acetonitrile solution, magnetically stirred at room temperature for 30 min, and 1 g of tetrabutylammonium hexafluorophosphate was added to prepare an electrolyte;

[0083] A three-electrode system was adopted, with the pretreated chemical foil D1 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode and the reference electrode were immersed in the electrolyte and subjected to the electrochemical polymerization reaction for 60 minutes under the condition of an oxidation current of 0.1 mA by the constant current method. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C under blown air for 20 minutes to obtain a high-density and high-stability conductive polymer film M2 based on electrochemical polymerization.

[0084] Preparation Example 3

[0085] A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization comprises the following steps:

[0086] 10 g of EDOT monomer was added to 100 mL of ethanol mixed solution, magnetically stirred at room temperature for 30 min, and 0.5 g of p-toluenesulfonic acid was added to prepare an electrolyte;

[0087] A three-electrode system was adopted, with the pretreated chemical foil D1 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode and the reference electrode were immersed in an electrolyte and subjected to cyclic voltammetry. An electrochemical polymerization reaction was carried out under the conditions of a voltage scanning range of 0-1.6V, a scanning rate of 50mV / s, and 50 cycles of scanning. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C under blown air for 20 minutes to obtain a highly dense and highly stable conductive polymer film M3 based on electrochemical polymerization.

[0088] Preparation Example 4

[0089] A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization comprises the following steps:

[0090] 1.5 g of EDOT monomer was added to 100 mL of ethanol: water mixed solution (the volume ratio of ethanol to water was 75:25), magnetically stirred at room temperature for 30 min, and p-toluenesulfonic acid was added to adjust the pH to 3 to prepare an electrolyte;

[0091] A three-electrode system was adopted, with the pretreated chemical foil D2 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode and the reference electrode were immersed in an electrolyte and subjected to cyclic voltammetry. An electrochemical polymerization reaction was carried out under the conditions of a voltage scanning range of 0-1.6 V, a scanning rate of 50 mV / s, and 100 cycles of cyclic scanning. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C in vacuum for 20 min to obtain a highly dense and highly stable conductive polymer film M4 based on electrochemical polymerization.

[0092] Preparation Example 5

[0093] A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization comprises the following steps:

[0094] 1.5 g of EDOT monomer was added to 100 mL of ethanol: water mixed solution (the volume ratio of ethanol to water was 75:25), magnetically stirred at room temperature for 30 min, and p-toluenesulfonic acid was added to adjust the pH to 3 to prepare an electrolyte;

[0095] A three-electrode system was adopted, with the pretreated chemical foil D2 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode and the reference electrode were immersed in an electrolyte and subjected to cyclic voltammetry. An electrochemical polymerization reaction was carried out under the conditions of a voltage scanning range of 0-1.6 V, a scanning rate of 50 mV / s, and 80 cycles of scanning. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C in vacuum for 20 minutes to obtain a highly dense and highly stable conductive polymer film M5 based on electrochemical polymerization.

[0096] Preparation Example 6

[0097] A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization comprises the following steps:

[0098] 1.5 g of EDOT monomer was added to 100 mL of ethanol: water mixed solution (the volume ratio of ethanol to water was 75:25), magnetically stirred at room temperature for 30 min, and p-toluenesulfonic acid was added to adjust the pH to 3 to prepare an electrolyte;

[0099] A three-electrode system was used, with the pretreated chemical foil D2 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode, and the reference electrode were immersed in an electrolyte and subjected to cyclic voltammetry. The electrochemical polymerization reaction was carried out under the conditions of a voltage scanning range of 0-1.6V, a scanning rate of 50mV / s, and a cycle scanning of 120 circles. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C in vacuum for 20min.

[0100] After drying, the above steps are repeated once (ie, a secondary electrochemical polymerization reaction is performed in the electrolyte again) to obtain a highly dense and highly stable conductive polymer film M6 based on electrochemical polymerization.

[0101] Preparation Example 7

[0102] A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization comprises the following steps:

[0103] 1.5 g of EDOT monomer was added to 100 mL of ethanol: water mixed solution (the volume ratio of ethanol to water was 75:25), magnetically stirred at room temperature for 30 min, and p-toluenesulfonic acid was added to adjust the pH to 3 to prepare an electrolyte;

[0104] A three-electrode system was adopted, with the pretreated chemical foil D5 as the working electrode, the platinum wire as the counter electrode, and the saturated calomel electrode as the reference electrode. The working electrode, the counter electrode and the reference electrode were immersed in an electrolyte and subjected to cyclic voltammetry. An electrochemical polymerization reaction was carried out under the conditions of a voltage scanning range of 0-1.6 V, a scanning rate of 50 mV / s, and 100 cycles of cyclic scanning. After the reaction, the working electrode was taken out, washed with deionized water, and dried at 80°C in vacuum for 20 min to obtain a high-density and high-stability conductive polymer film M7 based on electrochemical polymerization.

[0105] Test Example 1

[0106] SEM tests were performed on the pre-treated chemically formed foils D1-D6.

[0107] Test method: The test method familiar to people in the relevant field is adopted, and the test instrument model is: Thermo Fisher QuattroS spectrometer, EDAXELECTPIUS.

[0108] Conductive carbon paste was dipped on the surface of the pretreated chemical foils D1-D6, and then silver paste was dipped on the surface after curing at room temperature to prepare chip-type laminated aluminum electrolytic capacitors A1-A6. The capacitance extraction, equivalent series resistance (ESR), leakage current (LC), and high temperature and high humidity stability of the capacitors were tested.

[0109] Test method: The test method familiar to personnel in related fields is adopted, and the test instrument models are: Zhixin Precision, ZX8516B-1X and ZX6589-800V.

[0110] Test results such as Figure 1 As shown in Table 1, Figure 1 SEM photos of the thin films prepared in Preparation Examples D1-D6 are shown, and Table 1 shows the performance of aluminum electrolytic capacitors A1-A6 obtained based on the thin films prepared in D1-D6.

[0111] Table 1 Performance test results of capacitors A1-A6

[0112]

[0113] Note: The capacitor ESR stability test is a high temperature and high humidity stability test, the ambient temperature is 85±2℃, the ambient relative humidity is 85±3%RH, and the duration is 1000h.

[0114] Depend on Figure 1 It can be concluded from Table 1 that the pretreated chemical foil according to the present invention has a relatively rough and non-dense morphology structure, and the capacitors prepared therefrom need to be improved in terms of capacity extraction rate, ESR, LC and stability. However, the performance of the aluminum electrolytic capacitors A1-A5 prepared by the pretreated chemical foil according to the present invention is significantly better than that of the aluminum electrolytic capacitor A6.

[0115] Test Example 2

[0116] The conductive polymer films M1-M7 were subjected to SEM tests.

[0117] Test method: The test method familiar to people in the relevant field is adopted, and the test instrument model is: Thermo Fisher QuattroS spectrometer, EDAXELECTPIUS.

[0118] Conductive carbon paste was dipped on the surface of the high-density and high-stability conductive polymer films M1-M7 based on electrochemical polymerization, and then silver paste was dipped on the surface after curing at room temperature to prepare chip-type laminated aluminum electrolytic capacitors B1-B7. The capacitance extraction, equivalent series resistance (ESR), leakage current (LC), and high temperature and high humidity stability of the capacitors were tested.

[0119] Test method: The test method familiar to personnel in related fields is adopted, and the test instrument models are: Zhixin Precision, ZX8516B-1X and ZX6589-800V.

[0120] Test results such as Figure 2 As shown in Table 2, Figure 2 SEM photos of thin films prepared by implementation examples M1-M7 are shown, and Table 2 shows the performance of aluminum electrolytic capacitors B1-B7 obtained based on the implementation examples.

[0121] Table 2 Performance test results of capacitors B1-B8

[0122]

[0123] Note: The capacitor ESR stability test is a high temperature and high humidity stability test, the ambient temperature is 85±2℃, the ambient relative humidity is 85±3%RH, and the duration is 1000h.

[0124] Depend on Figure 2 It can be concluded from Table 2 that the film prepared according to the embodiment of the present invention has a flat and dense morphology structure, and the prepared capacitor has a higher capacity extraction rate, lower ESR, higher ESR stability and lower leakage current. Compared with the test results in Table 1, the performance and stability of the aluminum electrolytic capacitor prepared according to the method of the present invention have been comprehensively improved.

[0125] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0126] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization, characterized in that: The steps include: The forming foil is pretreated with a treatment solution to obtain a working electrode, and then the working electrode, the reference electrode and the counter electrode are immersed in an electrolyte, and electrochemical polymerization is performed through a three-electrode system to obtain a high-density and high-stability conductive polymer film based on electrochemical polymerization; in, The treatment solution is selected from an oxidant solution and a BFDO monomer solution; or The treatment solution is selected from PBFDO solution.

2. The method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization according to claim 1, characterized in that: The pre-processing comprises the following steps: The formed foil is immersed in the PBFDO solution and dried, and the process is repeated several times to obtain a pretreated formed foil; or The formed foil is immersed in an oxidant solution, dried, and then immersed in a BFDO monomer solution, dried, and repeated several times to obtain a pretreated formed foil; or The chemical foil is immersed in a BFDO monomer solution, dried, and then immersed in an oxidant solution, dried. After repeating this process several times, a pretreated chemical foil is obtained.

3. The method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization according to claim 2, characterized in that: The time for immersing the formed foil in the PBFDO solution is 4-20s; The time for the chemical foil to be immersed in the oxidant solution is 4-20s; The time for immersing the formation foil in the BFDO monomer solution is 4-20 seconds.

4. The method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization according to claim 1, characterized in that: The oxidant is selected from one or more of metal salt oxidants, oxides, peroxides, quinone compounds, and acid anhydride compounds.

5. The method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization according to claim 1, characterized in that: The electrochemical oxidative polymerization method adopts one of constant voltage method, constant current method and cyclic voltammetry method; in, In the constant voltage method, the oxidation potential is 0.3-3.0V, and the oxidation polymerization time is 5-200min; In the constant current method, the oxidation current is 0.1 μA-10 mA, and the oxidation polymerization time is 5-200 min; In the cyclic voltammetry method, the voltage scanning range is -1.0 to 3.0 V, the scanning rate is 20 to 100 mV / s, and the number of cycles is 10 to 5000.

6. The method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization according to claim 1, characterized in that: The electrolyte is selected from a solution containing EDOT monomer and its derivatives; Wherein, the concentration of the solution is 5-300 mg / mL.

7. The method for preparing a high-density and high-stability conductive polymer film based on electrochemical polymerization according to claim 1, characterized in that: The three-electrode system comprises a working electrode, a counter electrode and a reference electrode; Wherein, the working electrode is selected from the pre-treated chemical foil; The counter electrode is selected from one or more of platinum and graphite electrodes; The reference electrode is selected from one or more of a saturated calomel electrode, a silver chloride electrode, and a mercury / mercurous sulfate electrode.

8. Application of the high-density and high-stability conductive polymer film based on electrochemical polymerization prepared by the preparation method according to any one of claims 1 to 7 in the fields of supercapacitors and electrolytic capacitors.

Citation Information

Patent Citations

  • Method for improving cycle stability of polymer electrochromic film

    CN110592609A

  • N-type conjugated polymer as well as preparation method and application thereof

    CN115490835A

  • Chip-type laminated capacitor based on n-type conductive polymer and preparation method of chip-type laminated capacitor

    CN118430977A

  • Waterproof conductive coating and preparation method thereof

    CN118852905A

  • Manufacture of solid electrolytic capacitor

    JP1992034915A